Pop goes the weasel - Patterson, James (London : Headline Feature, 1999)
Detective Alex Cross is back- and he's in love. But his happiness is threatened by a series of chilling murders in Washington, D.C., murders with a pattern so twisted they leave investigators reeling. Cross's pursuit of the killer produces a suspect, a British diplomat named Geoffrey Shafer. But proving he's the murderer becomes a potentially deadly task. As Shafer engages in a brilliant series of surprising countermoves, Alex and his fiance become hopelessly entangled with the most memorable nemesis Cross has ever faced
Keywords: Police -- Fiction. -- United States; Serial murderers -- Fiction. -- United States